Tembang dalam Tradisi Orang Sunda: Kajian Naskah Guguritan Haji Hasan Mustapa - Dede Burhanudin (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2013)
The content of Guguritan Haji Hasan Mustapa deals with the dynamic of religious life of Sundanese. Through, Guguritan, members of community communicate each other by means of dialog. From the guguritan as a culture, it is manifestly that Sunda is an open cultural identity. Sunda and Sundanese also, have become the meeting point of their cultural identity. It was shown here by their pattern of reciprocal interaction and adaptation—both in group communication (makalangan) and adaptation to the change of the world (ngigelan zaman dan ngigelkeun zaman).Keywords: Tembang, Tradition, Guguritan Haji Hasan Mustapa